Observing and participating in social interactions: Action perception and action control across the autistic spectrum. (January 2018) - Bolis, Dimitris; Schilbach, Leonhard
Highlights: Sensory and social processes in autism are thought to be tightly connected. Social impairments in autism are related to difficulties in responding to, rather than in merely perceiving social cues. We argue for a multilevel perspective of social interaction, quantifying both individual and collective processes. We propose a two-person setup for studying the interrelation of sensory processing and interpersonal coordination. This setup will allow for a multilevel investigation of autism and other psychiatric disorders. Abstract: Autism is a developmental condition, characterized by difficulties of social interaction and communication, as well as restricted interests and repetitive behaviors. Although several important conceptions have shed light on specific facets, there is still no consensus about a universal yet specific theory in terms of its underlying mechanisms. While some theories have exclusively focused on sensory aspects, others have emphasized social difficulties. However, sensory and social processes in autism might be interconnected to a higher degree than what has been traditionally thought. We propose that a mismatch in sensory abilities across individuals can lead to difficulties on a social, i.e. interpersonal level and vice versa. In this article, we, therefore, selectively review evidence indicating an interrelationship between perceptual and social difficulties in autism. Additionally, we link this body of research with studies, which investigate the mechanisms of action control in social contexts. By doing so, we highlight that autistic traits are also crucially related to differences in integration, anticipation and automatic responding to social cues, rather than a mere inability to register and learn from social cues. Importantly, such differences may only manifest themselves in sufficiently complex situations, such as real-life social interactions, where such processes are inextricably linked.